MEDICAL SUPPORT IN THE COMPREHENSIVE TREATMENT OF GENERALIZED PERIODONTITIS (LITERATURE REVIEW) - І.І. Sokolova (Український стоматологічний альманах)
The purpose of the study is to analyze the scientific literature on the means and approaches to drug support in the complex treatment of generalized periodontitis.